Rapid Multiplication of Sugarcane Seedlings of PSJT 941 Variety from Tissue Culture Using Ethephon and Paclobutrazol - Arinta Rury Puspitasari; Aprilia Mutia Dewi; Sri Winarsih (Jurnal AgroBiogen, 2021)
Indonesia's sugar self-sufficiency was targeted since 2014 but the target has not been reached yet. One of the major constraints is the limited healthy seedlings available for new sugarcane area expansion. The mass production of healthy sugarcane seedlings may be achieved by rapid multiplication of tissue culture-derived seedlings using plant growth regulators (PGR) applied in the nursery house. The aim of this study was to determine the effect of ethephon and pacloburazol (PBZ) on the growth and seedling multiplication of sugarcane PSJT 941 variety. The research was carried out in the nursery house at Pasuruan Experimental Station, Indonesian Sugarcane Research Center. This study was arranged using a randomized block design with three replications. The treatments included (a) 3.5 ml/l ethephon, (b) 7.0 ml/l ethephon, (c) 1.5 ml/l PBZ, (d) 3.0 ml/l PBZ, and (e) control (without application of neither ethephon nor PBZ). The results showed that the highest number of shoots per clump was obtained from 3.0 ml/l PBZ treatment (8.7 shoots/clump) after 3 months of application. In the contrary, PBZ reduced the plant height compared with control and ethephon. Ethephon and PBZ treatments improved seed multiplication 8–52 times, much higher than the control that produced seed multiplication value six times. Further study is necessary to obtain optimal PBZ concentration for better stem height by decreasing the PBZ inhibition effect on stem growth.